First record of spongillaflies (Neuroptera: Sisyridae) from Colombia - Ardila-Camacho, Adrian; Martins, Caleb C. (Zootaxa, 2017)
The family Sisyridae (spongillaflies) is a small group of neuropterans distributed in all Biogeographic realms (Cover & Resh 2008). As in Nevrorthidae, Sisyridae is distinguished among other Neuroptera families by their strictly aquatic larvae (Wichard et al. 2002). The phylogenetic relationships of Sisyridae have been controversial i.e. the family was recovered at different positions within the Neuropterida phylogeny as a basal group among members of Neuroptera or whitin the suborder Hemerobiiformia with a very variable placement (Randolf et al. 2013). Currently the species richness of this group reaches 70 representatives in four genera, namely Climacia McLachlan, 1869 (New World), Sisyra Burmeister, 1839 (cosmopolitan), Sisyrina Banks, 1939 (Africa, Asia and Australia), and Sisyborina Monserrat, 1981 (endemic to Africa) (Parfin & Gurney 1956; Cover & Resh 2008).